Effectiveness of Mindfulness-based Therapy for Reducing Anxiety and Depression in Patients With Cancer: A Meta-analysis. Issue 45 (November 2015) - Zhang, Mei-Fen; Wen, Yong-Shan; Liu, Wei-Yan; Peng, Li-Fen; Wu, Xiao-Dan; Liu, Qian-Wen
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Anxiety and depression are common among patients with cancer, and are often treated with psychological interventions including mindfulness-based therapy. The aim of the study was to perform a meta-analysis of the effectiveness of mindfulness-based interventions for improving anxiety and depression in patients with cancer. Medline, the Cochrane Library, EMBASE, and Google Scholar were searched. The randomized controlled trials designed for patients diagnosed with cancer were included. Mindfulness-based interventions were provided. The outcomes assessed were the changes in anxiety and depression scores from before to after the intervention. The treatment response was determined by calculating the standardized mean difference (SMD) for individual studies and for pooled study results. Subgroup analyses by cancer type, type of therapy, and length of follow-up were performed. Seven studies, involving 469 participants who received mindfulness-based interventions and 419 participants in a control group, were included in the meta-analysis. Mindfulness-based stress reduction and art therapy were the most common interventions (5/7 studies). All studies reported anxiety and depression scores. The pooled SMD of the change in anxiety significantly favored mindfulness-based therapy over control treatment (−0.75, 95% confidence interval −1.28, −0.22, P = 0.005). Likewise, the pooled SMD of the change in depression also significantly favored mindfulness-based therapy over control (−0.90, 95% confidence interval −1.53, −0.26, P = 0.006). During the length of follow-ups less than 12 weeks, mindfulness-based therapy significantly improved anxiety for follow-up ≤12 weeks after the start of therapy, but not >12 weeks after the start of therapy. There was a lack of consistency between the studies in the type of mindfulness-based/control intervention implemented. Patients had different forms of cancer. Subgroup analyses included a relatively small number of studies and did not account for factors such as the severity of anxiety and/or depression, the time since diagnosis, and cancer stage. Mindfulness-based interventions effectively relieved anxiety and depression among patients with cancer. However, additional research is still warranted to determine how long the beneficial effects of mindfulness-based therapy persist.